A Chemical Route to Monolithic Integration of Crystalline Oxides on Semiconductors. Issue 8 (2nd May 2014) - McDaniel, Martin D.; Ngo, Thong Q.; Posadas, Agham; Hu, Chengqing; Lu, Sirong; Smith, David J.; Yu, Edward T.; Demkov, Alexander A.; Ekerdt, John G.
<x xml:space="preserve">Abstract</x> This work demonstrates the growth of crystalline SrTiO3 (STO) directly on germanium via a chemical method. After thermal deoxidation, the Ge substrate is transferred in vacuo to the deposition chamber where a thin film of STO (2 nm) is deposited by atomic layer deposition (ALD) at 225 °C. Following post‐deposition annealing at 650 °C for 5 min, the STO film becomes crystalline with epitaxial registry to the underlying Ge (001) substrate. Thicker STO films (up to 15 nm) are then grown on the crystalline STO seed layer. The crystalline structure and orientation are confirmed via reflection high‐energy electron diffraction, X‐ray diffraction, and transmission electron microscopy. Electrical measurements of a 15‐nm thick epitaxial STO film on Ge show a large dielectric constant (k ≈ 90), but relatively high leakage current of ≈10 A/cm2 for an applied field of 0.7 MV/cm. To suppress the leakage current, an aluminum precursor is cycled during ALD growth to grow crystalline Al‐doped STO (SrTi1‐xAlxO3‐δ) films. With sufficient Al doping (≈13%), the leakage current decreases by two orders of magnitude for an 8‐nm thick film. The current work demonstrates the potential of ALD‐grown crystalline oxides to be explored for advanced electronic applications, including high‐mobility Ge‐based transistors.